2021
DOI: 10.3390/molecules26061657
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes and Phenolic Compounds from the Fungus Fuscoporia torulosa: Isolation, Structure Determination and Biological Activity

Abstract: Investigation of the methanol extract of the poroid fungus Fuscoporia torulosa resulted in the isolation of a novel triterpene, fuscoporic acid (1), together with inoscavin A and its previously undescribed Z isomer (2 and 3), 3,4-dihydroxy-benzaldehide (4), osmundacetone (5), senexdiolic acid (6), natalic acid (7), and ergosta-7,22-diene-3-one (8). The structures of fungal compounds were determined on the basis of NMR and MS spectroscopic analyses, as well as molecular modeling studies. Compounds 1, 6–8 were e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…CWEs possessed lower scavenging activity, with P. torulosus as more efficient ABTS scavenger. Reports for the chemical composition of methanol extracts of P. torulosus revealed that phenolic compounds (mostly 3,4‐dihydroxy‐benzaldehide and osmundacetone) possess the most potent DPPH scavenging potentials (Béni et al, 2021). However, it seems that in HWEs, additional scavengers are present since published results for DPPH radical scavenging activity of P. igniarius , P. nigricans , and P. linteus have weaker correlation with their phenolic content, when compared with their ethanolic extracts (Thammavong et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…CWEs possessed lower scavenging activity, with P. torulosus as more efficient ABTS scavenger. Reports for the chemical composition of methanol extracts of P. torulosus revealed that phenolic compounds (mostly 3,4‐dihydroxy‐benzaldehide and osmundacetone) possess the most potent DPPH scavenging potentials (Béni et al, 2021). However, it seems that in HWEs, additional scavengers are present since published results for DPPH radical scavenging activity of P. igniarius , P. nigricans , and P. linteus have weaker correlation with their phenolic content, when compared with their ethanolic extracts (Thammavong et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“… 7 The fungal metabolite ergosta-7,22-diene-3-one was found to be effective against sensitive (Colo 205) and resistant (Colo 320) human colon adenocarcinoma cells with IC 50 values 11.6 ± 1.7 μM and 8.4 ± 1.1 μM, respectively, and in a combination assay synergism was detected between ergosta-7,22-diene-3-one and doxorubicin with CI index 0.521 ± 0.15 at the 50% growth inhibition dose (ED 50 ). 8 …”
mentioning
confidence: 99%
“…Compounds 1−6 were inactive against Escherichia coli ATCC 25922, Salmonella enterica serovar Typhimurium 14028s, Staphylococcus aureus ATCC 25923, and S. aureus 27213 8. …”
mentioning
confidence: 99%
“…The literature shows that O. japonica possesses a variety of biological activities, especially its antioxidant capacity, which showed excellent performance in the β-carotene-linoleic acid test, the DPPH free radical scavenging assay, the ABTS cation radical scavenging assay and the cupric reducing antioxidant capacity assay and good metal-chelating activity in the Fe 2+ assay (Beni et al, 2021). It has also been proven to reduce the accumulation of reactive oxygen species in animal studies.…”
mentioning
confidence: 99%